Biochemical characterization of stallion prostasomes and comparison to their human counterparts. (December 2013) - Ronquist, Göran K.; Ek, Bo; Ronquist, Gunnar; Morrell, Jane; Carlsson, Lena; Larsson, Anders
<x xml:space="preserve">Abstract</x> Release of nanometer-sized prostasomes into human and equine semen suggests essential functions in their relationships with sperm cells and the fertilization process. The two types of prostasomes displayed ultrastructural similarities, albeit the human prostasomes were somewhat larger than the stallion prostasomes. A high ratio of saturated fatty acids was characteristic for the two prostasome types. Electrophoretic separation systems revealed an equine prostasomal pattern different from that of human. The 21 distinctive low molecular weight protein spots in the 2D-gel (with no counterparts in human prostasomes) were identified via peptide mass fingerprinting, several of which may be different isoforms. Out of the three high molecular weight bands characteristic for human prostasomes (CD10, CD13, and CD26), CD10 and CD13 were retrieved in equine prostasomes. We present some new proteins of horse prostasomes not found in their human counterparts. Further studies are warranted to reveal the function of these proteins.